2015
DOI: 10.1007/s13318-015-0287-0
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Profile of Isocorynoxeine in Rats Obtained by Ultra-High Performance Liquid Chromatography/Quadrupole Time-of-Flight Mass Spectrometry

Abstract: The result indicates that IC undergoes extensive metabolism in vivo, mainly including hydrolysis, oxidation, isomerization, demethylation, epoxidation, reduction, glucuronidation, hydroxylation and N-oxidation, which is helpful for the further pharmacokinetic study of IC in vivo.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 21 publications
2
7
0
Order By: Relevance
“…M19 was tentatively identified as a reduction and demethylation metabolite of GM (P27) or HTE (P28). According to our previous studies (Qi et al, ; Zhao et al, ), we also found that ICO (P15) and COR (P17) could be converted into IRN (P16) and RIN (P19) by a reduction reaction in vivo , respectively. However, none of the epoxidation and N ‐oxidation metabolites of ICO were found in this study.…”
Section: Resultssupporting
confidence: 66%
See 3 more Smart Citations
“…M19 was tentatively identified as a reduction and demethylation metabolite of GM (P27) or HTE (P28). According to our previous studies (Qi et al, ; Zhao et al, ), we also found that ICO (P15) and COR (P17) could be converted into IRN (P16) and RIN (P19) by a reduction reaction in vivo , respectively. However, none of the epoxidation and N ‐oxidation metabolites of ICO were found in this study.…”
Section: Resultssupporting
confidence: 66%
“…M13 (retention time, t R 4.14 min), M16 ( t R 5.15 min), M18 ( t R 5.61 min) and M23 ( t R 6.19 min) exhibited the [M + H] + ions at m/z 369.1839, 369.1839, 369.1799, 369.1799 with the same molecular formula, speculated to be C 21 H 24 N 2 O 4 , and they were 14 Da (‐CH 2 ) lower than that of ICO (P15) or COR (P17). Comparing the retention time, accurate mass and diagnostic fragment ions with those of our previous studies (Yuan et al, ; Zhao et al, ), M13, M16, M18 and M23 were tentatively identified as isocorynoxeinic acid, 18,19‐dehydrocorynoxinic acid, corynoxeinic acid and 18,19‐dehydrocorynoxinic acid B, respectively, which were hydrolyzed metabolites of ICO (P15) or COR (P17). When identifying the tetracyclic oxindole alkaloids possessing a 7S configuration, there were two diagnostic fragmentation ions, m/z 201 (C 12 H 13 N 2 O) and 187 (C 11 H 11 N 2 O), which were reported in our previous studies (Qi, Chen, Sun, Simpkins, & Yuan, ; Zhao et al, ).…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Although the pharmacokinetic characteristics of isocorynoxeine given by oral administration in rat had been revealed in recent years, no study on the i.p. administration in vivo until now has been investigated [18,19]. In order to further understand the absorption and distribution of isocorynoxeine by i.p.…”
Section: Introductionmentioning
confidence: 99%